Pengaruh Media Terhadap Kesadaran Kesehatan Mental Mahasiswa Akuntansi: Mediasi Pengetahuan dan Sikap - Badriatu Sifri; Budi Barata Kusuma Utami (Value: Jurnal Manajemen dan Akuntansi, 2025)
WHO revealed that 14% of the population in the world has mental health problems. The problem can occur to students who have academic pressure such as accounting students in Indonesia. This study aims to examine the effect of media on mental health awareness among accounting students, with the mediating role of mental health knowledge, knowledge of professional help, and mental health attitudes, using social learning theory among accounting students in Indonesia. The sample for this study consists of accounting students in Indonesia, selected using the convenience sampling technique. The primary data used in this study were directly obtained from respondents through a questionnaire, with a total of 153 respondents. The data analysis method employed is Structural Equation Modeling Partial Least Square (SEM-PLS) using Smart PLS software version 3.0. The results of the analysis show that media, the mediating role of mental health knowledge, and mental health attitudes influence mental health awareness among accounting students. However, knowledge of professional help does not have a significant effect and does not mediate mental health awareness among accounting students in Indonesia.